Communication issues within high performance computing grids. (2nd May 2007) - McLeod, Robert D.; Hussain, Sajid; Huang, Sheng; Laskowski, Marek
This paper presents several ideas pertaining to desirable properties associated with protocols for moving large amounts of data over a grid of high performance computers. The protocol enhancements are discussed in terms of their scalability and identifying sources of potential protocol redundancy. In the context of this paper it is scalability as it relates to the transport of increasingly larger amounts of data over grid computing networks. Specifically we address efficacy in moving large data sets between nodes on a grid interconnected over a Wide Area Network (WAN) in terms of increasing the basic packet size and better suited to transport protocols. In addition we introduce a means of better evaluating error detection models as functions of increased packet size.